PEMBELAJARAN MEMBACA PEMAHAMAN DENGAN METODE COMPUTER ASSISTED LANGUAGE LEARNING (CALL) MELALUI CD INTERAKTIF BERORIENTASI KEARIFAN LOKAL - Witri Annisa (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
Reading comprehension of students is still low due to lack of interest and motivation of studentsin reading. Learning reading skills can take advantage of advances in technology with the application of methods through media interesting and effective. The use of attractive and effective method can increase interest and motivation to read. Efforts should be made to improve students' reading comprehension can through computer-based learning.Computer- based learning was conducted using Computer Assisted Language Learning (CALL) through the production of a CD Interkatif. Through advances in technology, students still know the culture of the nation by giving a discourse with the theme of local wisdom in every rubric magazine packed in the interactive CD.